Strategi Manajemen Kardiomiopati Peripartum: Perkembangan Dalam Menghadapi Tantangan Kesehatan Maternal - Setyowati, Danti Utami; Mayangsari, Veny; Tjahjono, Cholid (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Cardiomyopathies are uncommon, although they are significant contributors to serious cardiovascular problems during pregnancy. Prior to pregnancy, it is crucial to have a thorough understanding of the potential dangers linked to cardiomyopathies and how to effectively treat them in pregnant women with significant pre-existing diseases. This knowledge is essential for providing appropriate guidance to patients. Given that all interventions relate to both the mother and the fetus, it is crucial to focus on providing the most efficient care for both. Maternal illness complicates pregnancy in approximately 1-4% of instances. There is a lack of comprehensive data on the frequency and occurrence of heart disease connected to pregnancy in most regions of the world including peripartum cardiomyopathy (PPCM) which was the predominant causes of maternal mortality in the UK in the mid of 2000’s. PPCM may result in persistent systolic dysfunction over an extended period of time. Although heart disease is a prominent, if not the primary, cause of death among pregnant or postpartum women across the country. PPCM is frequently misdiagnosed as a result of insufficient awareness among both medical professionals and the general public. The absence of an early and precise diagnosis of this ailment can have life-threatening implications for women affected by PPCM. Patients who had an early diagnosis saw a more expedited recovery compared to patients who received a late diagnosis. Improving the early monitoring, detection and diagnosis is linked to better recovery.